Factors Influencing Consumer Choices and Organic Food Production in Haryana: Insights from Farmers - Yadav, Ekta; Megha Goyal,; Suman Ghalawat,; Joginder Singh Malik,; Monika Devi,; Vinay Mehala, (Indian Journal of Extension Education, 2024)
The study examined consumer behaviour dynamics in Haryana related to organic food purchases and forecasted production, in 2023-2024. The research employed area sampling; representing four districts based on organic food store availability, and surveyed 300 consumers during 2024. Three key factors influencing purchasing decisions were identified: benefits of organic food, characteristics of organic food, and promotional tools. The Benefits of organic food, explaining 30.461% of the variance, was the most significant, emphasizing health advantage, environmental protection, and trust in organic labels. Characteristics of organic food contributed 19.197% of the variance, focusing on quality, affordability, and chemical-free production. Promotional tools; accounting for 14.172%, highlighted discounts, taste, and online marketing. These factors collectively explained 63.830% of consumer decision-making, with health and environmental benefits emerging as primary motivators. The study forecasted organic food production in Haryana from 2011-12 to 2022-23 using polynomial regression analysis, with a moderate model fit (R² = 0.60). The findings revealed significant production fluctuations due to external factors, suggesting the need for continued research to improve forecast accuracy.